Aplicação da teoria das Cadeias Meios-Fins (MEC) no estudo do consumo do parto humanizado - Silva, Lair Barroso Arraes Rocha (2016)
In parallel to the growth of products and services that appeal to a healthier lifestyle search, also grows the consciousness that the consumption of those is not only for the utility functions, but also because of the symbolic functions, being that knowledge a very important tool for entrepreneurs and marketing professionals in the strategy creation process. This thesis had as goal the search of the humanized birth consumption motivation, under the Means-End Chain Theory, having as reference the predicate and benefits identification awaited with the humanized birth consumption, regarding to the consumer's values. The theoretical support is based on a marketing research regarded to the consumers behave, consumption motivation, consumer's goals and the Mean-End Chain Theory, and sought the psychology field to perceive human values. The quantity research used the laddering to interview 32 women. the high number of attributes, consequences and identified numbers, revealed the complex structure that characterize the cognitive perspective of this consumer group. Based on the results of interviews conducted, it is concluded that the main values that guide the consumers buying decision are "the security", "the self-direction" and "the achievement", implying that these women are guided by individual nature values aiming, firstly, the satisfaction of the woman herself. Moreover, it was possible to identify the hospital humanized birth is the expensive child-bearing option, followed by elective caesarean section and, finally, the humanized home delivery. Thus, the status also appears as one of the reasons for the intention to hold a humanized birth, since without financial resources, within the supplementary and private health system, delimitation of this research, it is not possible to get a humanized birth these days. Thereby, values like "security" and "achievement" appear associated with the issue of the status that the price of labor brings. It was also noted that the group has great influence on the consumers' behavior and gender issues permeating consumption. Regarded to advertising strategies, it is suggested to be leaded to the expected benefits from costumers. As regards the technique, the laddering was shown to be a very efficient tool for evaluation of motivation in the high involvement consumption.